Assessment of change in forests land, carbon stock and carbon emissions of KPK, Pakistan for past three decades using geospatial techniques. Issue 2 (27th January 2023) - Goheer, Muhammad Arif; Fatima, Laraib; Farah, Humera; Hassan, Sher Shah; Abbas, Nazir
Abstract: Reducing emissions from deforestation and forest degradation is a mechanism to cut down GHG emissions and protect the threatened forest ecosystems. Pakistan is suffering from high forest degradation and deforestation rates, but recent plantations under BTTAP have created a significant impact. This study was designed to identify the LULC changes, forest sequestration and emissions from forest degradation in the forest hub districts (Malakand, Mardan, Lower Dir and Upper Dir) of KPK, Pakistan using Landsat imageries. LULC changes were analyzed from 1990 to 2020. In addition, the amount of carbon sequestration and emissions from forest degradation were also calculated. Results of the analysis showed forest area reduction from 1990 to 2009, followed by a sharp increase in the next decade (2010–2020) by 56%. Around 836 km 2 of land was found to be covered with forests during BTTAP. The net change was a 32% increase in forest land over three decades. The study offers important information which environment managers and decision-makers can utilize to encourage the plantation of trees and save existing forests in the country to combat climate change. HIGHLIGHTS: Forest area reduced from 1990 to 2009, and a sharp increase was seen in the next decade (between 2009 and 2020) by 56%. Almost 836 km 2 of land was found to be covered with forests. The net change was recorded as a 32% increase in forest land in the study area over three decades. From 1990 to 2000, 1.3 tons of carbon stock was degraded. From 2000 to 2009, 3.4 tons of carbon stock degraded. Graphical Abstract